Clinical and Optic Disc Characteristics of Patients Showing Visual Recovery in Leber Hereditary Optic Neuropathy. Issue 1 (March 2020) - Moon, Yeji; Kim, Ungsoo S.; Han, Jinu; Ahn, Hyosook; Lim, Hyun Taek
Abstract : Background: The visual prognosis in Leber hereditary optic neuropathy (LHON) is generally poor. However, some individuals can have spontaneous visual recovery (VR) in one or both eyes by a mechanism that is not yet clearly understood. The purpose of this study was to determine whether certain clinical and optic disc features are associated with VR in patients with LHON. Methods: We retrospectively examined 80 eyes of 40 patients with LHON using clinical databases, fundus photographs, and high-definition spectral-domain optical coherence tomography (OCT) images. VR was defined as a gain of 3 or more lines of logarithm of the minimum angle of resolution (logMAR)–scaled visual acuity from nadir; this represents a doubling of the visual angle. Patients were divided into VR and nonrecovery (NR) groups. Using fundus photographs, we measured optic disc size and evaluated for the presence of optic disc features, including peripapillary telangiectasia, disc hyperemia, and swelling. We also measured the disc area, cup-to-disc ratio, and rim area of the optic disc using OCT. Results: Twenty-one of 80 eyes (26%) had a VR. The VR occurred within 2 years after onset in 81% of cases. The VR group showed younger age at onset (21 vs 29 years, P = 0.017) and better visual acuity at the nadir (1.39 vs 2.16 logMAR, P < 0.001) compared with the NR group. Optic disc features, particularly peripapillary telangiectasia ( P = 0.027) and disc hyperemia ( P = 0.006), were more prominent in the NR group. The cup-to-disc ratio was significantly smaller (0.64 vs 0.71, P = 0.004) and the rim area was significantly greater (1.17 vs 0.85 mm 2, P < 0.001) in the VR group compared with the NR group. Conclusions: A younger age at onset and a less severe reduction of visual acuity at the nadir were associated with a higher probability of VR. Presence of peripapillary telangiectasia and optic disc hyperemia may serve as predictive factors for poor visual prognosis in patients with LHON.